Phosphorylation of epidermal growth factor receptor at serine 1047 in cultured lung alveolar epithelial cells by bradykinin B2 receptor stimulation. (February 2018) - Izumi, Shunsuke; Higa-Nakamine, Sayomi; Nishi, Hiroyuki; Torihara, Hidetsugu; Uehara, Ayako; Sugahara, Kazuhiro; Kakinohana, Manabu; Yamamoto, Hideyuki
Abstract: Accumulating evidence indicates that epidermal growth factor receptor (EGFR) is desensitized by phosphorylation of serine 1047 (Ser1047). We and other groups have reported that stimulation of a receptor of tumor-necrosis factor α (TNFα) and Toll-like receptor 5 (TLR5) induced the phosphorylation of Ser1047 through activation of p38 mitogen-activated protein kinase (p38 MAPK) in cultured lung alveolar epithelial A549 cells. However, phosphorylation of EGFR at Ser1047 by stimulation of any G-protein coupled receptors (GPCRs) has not been reported in any cultured cells. In the present study, we first confirmed that A549 cells expressed bradykinin (BK) B2 receptor, and then, we examined whether BK treatment of A549 cells activated MAPKs and induced the phosphorylation of EGFR at Ser1047. Immunoblotting analysis and reporter gene assays indicated that BK activated the pathways of extracellular signal-regulated kinase (ERK) and p38 MAPK. Inhibitor studies suggested that Gq/11 was mainly involved in the activation of ERK and p38 MAPK. We found that stimulation of the BK B2 receptor, but not the BK B1 receptor, induced phosphorylation of EGFR at Ser1047. Pharmacological experiments indicated that both ERK and p38 MAPK were involved in the phosphorylation of EGFR. These results strongly suggested that BK regulates EGFR functions in lung alveolar epithelial cells. In addition, we found that BK treatment increased the mRNA level of dual specificity MAPK phosphatase 5 (DUSP5) in an ERK-dependent manner, which suggested that a negative feedback mechanism of ERK existed in the cells.